2015
DOI: 10.1242/jcs.171843
|View full text |Cite
|
Sign up to set email alerts
|

Altering lamina assembly identifies lamina-dependent and -independent functions for A-type lamins

Abstract: Lamins are intermediate filament proteins that form a fibrous meshwork, called the nuclear lamina, between the inner nuclear membrane and peripheral heterochromatin of metazoan cells. The assembly and incorporation of lamin A/C into the lamina, as well as their various functions, are still not well understood. Here, we employed designed ankyrin repeat proteins (DARPins) as new experimental tools for lamin research. We screened for DARPins that specifically bound to lamin A/C, and interfered with lamin assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 69 publications
2
33
1
Order By: Relevance
“…Lmna-knockout mice lack both peripheral and nucleoplasmic lamins, and it is difficult to assign the observed phenotypes to the loss of a specific pool. LAP2α-deficient mice (Naetar et al, 2008), mice that express assembly-deficient lamin A mutants (Bertrand et al, 2012) or cells that express lamindisassembling DARPins (Zwerger et al, 2015), are probably the best experimental systems currently available, but these proteins or reagents might have additional lamin-independent or dominantnegative effects. Thus, the identification and development of new tools to specifically analyze lamins in the nuclear interior and their functions represent one of the key future challenges that are needed to unravel specific functions and roles of nucleoplasmic lamins in laminopathic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lmna-knockout mice lack both peripheral and nucleoplasmic lamins, and it is difficult to assign the observed phenotypes to the loss of a specific pool. LAP2α-deficient mice (Naetar et al, 2008), mice that express assembly-deficient lamin A mutants (Bertrand et al, 2012) or cells that express lamindisassembling DARPins (Zwerger et al, 2015), are probably the best experimental systems currently available, but these proteins or reagents might have additional lamin-independent or dominantnegative effects. Thus, the identification and development of new tools to specifically analyze lamins in the nuclear interior and their functions represent one of the key future challenges that are needed to unravel specific functions and roles of nucleoplasmic lamins in laminopathic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As LAP2α and nucleoplasmic lamin A affect the association between HMGN5 and chromatin (Zhang et al, 2013) and also chromatin mobility (Bronshtein et al, 2015), it is tempting to speculate that structures comprising A-type lamins and LAP2α contribute to the mechanical properties of the nucleus indirectly through their effect on spatial chromatin organization. In line with this hypothesis, a study that used genetically engeneered designed ankyrin-repeat proteins (DARPins) that disassemble lamins in living cells showed that these cells have a higher nuclear stiffness compared to LMNAknockout cells (Zwerger et al, 2015). However, this study also showed that nuclei with disassembled lamins are considerably softer than control nuclei in which the majority of lamins assembled at the nuclear lamina, suggesting that the peripheral lamina is particularly relevant for nuclear stiffness, whereas nucleoplasmic lamins can fine-tune the mechanical response of nuclei through changes in chromatin organization.…”
Section: Mechanical Functions Of Laminsmentioning
confidence: 92%
“…A list of antibodies, plasmids and cell lines used is presented in Supplementary Table 1 [30][31][32] .…”
Section: Methodsmentioning
confidence: 99%
“…It remains largely unasked how the lamina impacts the various membrane remodeling events that have recently been revealed to be essential for maintaining NE composition, organization, function, dynamics and quality control (QC) [15]. It is clear that nuclear mechanics scale with the mechanical environment in which the cell resides (so-called “mechanoreciprocity” [32,33]), thereby establishing distinct mechanical “set points” driven by global differences in lamin A expression level and/or turnover [33-35], the degree of lamin A phosphorylation on serine 22 ([35]; the classic “mitotic”, pro-disassembly modification [36,37]), the lamin assembly state [38] and the extent of lamina-associated heterochromatin [39,40]. To accommodate different mechanical set points, local remodeling of the nuclear lamina could be achieved by driving lamin A Ser22 phosphorylation (and potentially the phosphoregulation of other lamina components), in direct analogy to the spectrin phosphorylation that makes the erythrocyte membrane permissive to endocytosis (Fig.…”
Section: Introductionmentioning
confidence: 99%